ORGANIZING THE PEDAGOGICAL PROCESS FOR THE FORMATION OF CREATIVE AND CRITICAL THINKING SKILLS IN STUDENTS MECHANISMS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, the conditions and features of organizing the pedagogical process that trains students to think creatively, didactic situations related to the formation of creative thinking skills in students, their unique aspects, the sources of the formation of creative thinking skills, the role of educational content in the formation of creative thinking skills in students, the nature of tasks, creative aspects of thinking related to mental processes, and specific directions are discussed in detail. The views of educators and psychologists in this direction are described. This article can be widely used by the scientific and pedagogical communities, science teachers, doctoral students, and basic doctoral students.